2022
DOI: 10.1126/sciadv.abn0035
|View full text |Cite
|
Sign up to set email alerts
|

Deep ocean microbial communities produce more stable dissolved organic matter through the succession of rare prokaryotes

Abstract: The microbial carbon pump (MCP) hypothesis suggests that successive transformation of labile dissolved organic carbon (DOC) by prokaryotes produces refractory DOC (RDOC) and contributes to the long-term stability of the deep ocean DOC reservoir. We tested the MCP by exposing surface water from a deep convective region of the ocean to epipelagic, mesopelagic, and bathypelagic prokaryotic communities and tracked changes in dissolved organic matter concentration, composition, and prokaryotic taxa over time. Proka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 91 publications
1
15
0
Order By: Relevance
“…Natural DOM in the deep ocean is a complex mixture of organic molecules. , Characterizing the molecular composition of marine DOM and its bioavailability is a critical factor required to address this uncertainty but has received little attention in previous studies. Though previous related incubation experiments have applied solid-phase extraction to isolate natural DOM and tested its bioavailability, their conclusions have been inconsistent. ,,, It is unclear whether distinct commercial sorbents applied to extract DOM can explain this inconsistency.…”
Section: Introductionmentioning
confidence: 99%
“…Natural DOM in the deep ocean is a complex mixture of organic molecules. , Characterizing the molecular composition of marine DOM and its bioavailability is a critical factor required to address this uncertainty but has received little attention in previous studies. Though previous related incubation experiments have applied solid-phase extraction to isolate natural DOM and tested its bioavailability, their conclusions have been inconsistent. ,,, It is unclear whether distinct commercial sorbents applied to extract DOM can explain this inconsistency.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggest that oxygen-and nitrogen-enriched MFs are attributed to microbial and phytoplanktonic-related processes. 58,59 Therefore, our results indicate that microbial transformation and primary production processes could be the main regulated factors when DOM is transferred from land to ocean.…”
Section: Geochemical Interpretation Behind Machinementioning
confidence: 78%
“…Recent studies reported the complexing to organic ligands significantly reduce the bioavailability, bioaccumulation, and toxicity of REEs in aquatic ecosystems. , These reports highlight the significance of accounting for REE speciation in toxicity experiments, which is largely neglected in the literature, and further ecotoxicity studies on REEs are needed can help develop a environmental risk assessment criteria . REE–DOC interactions are another factor needing further research: DOM composition drives a wide range of global biogeochemical cycles. Metal complexation can affect DOM-mediated processes, and photochemistry is an environmental driver of DOM composition. ,,,, There is considerable uncertainty over how boreal soil–aquatic–marine system interactions will change over the coming years due to onset of rapid deglaciation and permafrost thaw. As new stores of subbituminous coal are released from landslides and terrestrial throughfall into the marine environment, photochemistry, as a process, may affect increased REE bioavailability in the oceans.…”
Section: Resultsmentioning
confidence: 99%